Explanation Of Oronyms And Orographic Terms Of Kashkadarya Region - Tojievich, Eshboev Bekhzod; Geldiyarovich, Nazarov Maksud (The journal of contemporary issues in business and government, 2021)
The article analyzes the formation of oronyms of Kashkadarya region and the reflection of the natural conditions of the region in place names. This region is distinguished by the richness and diversity of oronyms in Uzbekistan. In this study, each of the major oronyms in the region is described geographically and etymologically. A total of 312 oronyms were collected on the basis of a 1: 100.000 scale topographic map of Kashkadarya region, which were studied in groups, and their geographical features were determined. The natural-geographical terms that formed the oronyms of Kashkadarya region are described.